Academics appreciate awards: a new aspect of incentives in research - Bruno S. Frey; Susanne Neckermann (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper analyzes awards as a means of motivation prevalent in the scientific community, but so far neglected in the economic literature on incentives, and discusses their relationship to monetary compensation. Awards are better suited than performance pay to reward scientific tasks, which are typically of a vague nature. They derive their value, for instance, from signaling research talent to outsiders. Awards should therefore be taken seriously as a means of motivating research that may complement, or even substitute for, monetary incentives. While we discuss awards in the context of academia, our conclusions apply to other principal-agent settings as well.
Keywords: C93; J33; M52; 330; Awards; money; incentives; academia; research; Preisverleihung; Leistungsanreiz; Wissenschaftler; Wissenschaft; Agency Theory; Theorie